Ultra-broadband non-degenerate guided-wave bi-photon source in the near and mid-infrared - F Roeder; A Gnanavel; R Pollmann; O Brecht; M Stefszky; L Padberg; C Eigner; C Silberhorn; B Brecht (New Journal of Physics)
The latest applications in ultrafast quantum metrology require bright, broadband bi-photon sources with one of the photons in the mid-infrared and the other in the visible to near infrared. However, existing sources based on bulk crystals are limited in brightness due to the short interaction length and only allow for limited dispersion engineering. Here, we present an integrated PDC source based on a Ti:LiNbO _3 waveguide that generates broadband bi-photons with central wavelengths at $860\,nm$ and $2800\,nm$ . Their spectral bandwidth exceeds $25\,THz$ and is achieved by simultaneous matching of the group velocities (GVs) and cancellation of GV dispersion for the signal and idler field. We provide an intuitive understanding of the process by studying our source’s behavior at different temperatures and pump wavelengths, which agrees well with simulations.